VERBAL HUMOR FOUND IN AJO BUSET SONGS AND NEDI GAMPO SONGS - Yessi Mandasari Saragi; Hamzah Hamzah; Fitrawati Fitrawati (Universitas Negeri Padang, 2018)
Humor is a kind of communication phenomenon in which a person is able to see a funny side that can make him or her laugh. Verbal humor is a humor that expressed verbally. There are 8 types of verbal humor to analyze the verbal humor found in Ajo buset songs and Nedi gampo songs. The researcher used descriptive qualitative method. The data were collected by downloading Ajo buset and Nedi gampo songs, listen to them repeatedly, identifying and putting them on table. The data were also analyzed by classifying the data, analyzing the data, deciding the research findings, and drawing the conclusion. The result in this research there are 37 verbal humor found in Ajo buset songs: pun (31,58%), satire (7,88%), parody (2,63%), Anecdote (10,52%), Irony (10,52%), Sarcasm (13,16%), tall tale (21,01%) and 30 verbal humor found in Nedi gampo songs: pun (26,67%), satire (36,67%), sarcasm (23,33%), and tall tale (13,33%). Then, there are 3 differences found between Ajo buset songs and Nedi gampo songs. First, Ajo buset songs are more modern than Nedi gampo songs. Second, Ajo buset songs make people laugh without purposes, while Nedi gampo songs give social critics. Last, Ajo buset songs are used many exaggeration and Nedi gampo used exaggeration minimally.